PENGARUH KEPEMIMPINAN, ORGANIZATIONAL CITIZENSHIP BEHAVIOUR, DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA PEGAWAI - Wiwik Susilowati, Edi Wibowo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
ABSTRACT The purpose of this research is to analysis significance effect: (1) leaderships to the job satisfaction, (2) organizational citizenship behavior to the job satisfaction, (3) organizational commitment to the job satisfaction, (4) dominant variable effect to the job satisfaction. Populations in this research are employees of Youth, Sport, Culture, Tourism Department of Grobogan as many as 115 persons, amount of sample is 53 persons with proportional cluster random sampling method. The analysis result show: (1) The regressions equation is Y = 3,003 + 0,430 X1 + 0,241 X2 + 0,301 X3; (2) The result t test of leaderships has significance less than 0,05, the result t test of organizational citizenship behavior variable has significance less than 0,05, the result t test of organizational commitment variable has significance less than 0,05, it means that leaderships, organizational citizenship behavior and organizational commitment variable have significance effect to the job satisfaction. Determination coefficient (R2) test is 0,720, it means that the leaderships, organizational citizenship behavior, and organizational commitment are explain as 72% of the employee’s performance only, further more influenced by the other variables. Keywords: leaderships, organizational citizenship behavior, organizational commitment, job satisfaction